Answer:
Step-by-step explanation:
Explicit formula of the sequence,











Answer: x = 4 and y = -3
Step-by-step explanation:
2x + 4y = -4
2x = -4 - 4y
x = -2 - 2y
Now that we have solved the first equation for x, we plug (-2 - 2y) into the other equation in place of x and then solve for y.
3(-2 -2y) + 5y = -3
-6 - 6y + 5y = -3
-y = 3
y = -3
Now that we know y, we plug it into the original equation and solve for x.
2x + 4(-3) = -4
2x + -12 = -4
2x = 8
x = 4
You can check the answer by plugging both x and y into either of the original equations.
Answer:
y=7x+8
Step-by-step explanation:
Find the slope of the original line and use the slope-intercept form
Answer:
Good for Megan but what’s the question?
Step-by-step explanation: